Educators in the Islamic Concept: Its Implementation for Islamic Religious Education Teachers in Elementary Schools - Basyir, Fauziyah Amini; Samad, Duski; Batubara, Juliana (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Islamic education places educators as the primary figures in the formation of morals, character, and spiritual development of students, especially at the elementary school level. This article aims to explain the concept of educators in Islam, which includes the roles of muaddib, murabbi, muallim, muzakki, and mursyid, and analyze its application by Islamic Religious Education teachers in elementary schools. This study uses a qualitative approach through field research, with data collection techniques in the form of observation, structured interviews, and documentation. Research informants include Islamic Religious Education teachers, the principal, the teacher council, students, and parents at Padang Sago 06 Public Elementary School, Padang Pariaman Regency, Indonesia. Data were analyzed through a process of reduction, presentation, and verification to obtain a complete picture of the implementation of the concept of Islamic educators in learning practices. The results of the study indicate that Islamic Religious Education teachers have implemented Islamic educational values ​​through exemplary behavior, fostering good manners, developing student potential, delivering knowledge systematically, and spiritual guidance. The implementation of educators' roles as muaddib, murabbi, muallim, muzakki, and mursyid has a positive impact on strengthening students' religious character, discipline, and social behavior. These findings imply the importance of improving the capacity of Islamic Religious Education teachers to further integrate Islamic educational values ​​into the learning process in elementary schools.